Transcranial Direct Current Stimulation Over the Primary and Secondary Somatosensory Cortices Transiently Improves Tactile Spatial Discrimination in Stroke Patients - Fujimoto, Shuhei; Kon, Noriko; Otaka, Yohei; Yamaguchi, Tomofumi; Nakayama, Takeo; Kondo, Kunitsugu; Ragert, Patrick; Tanaka, Satoshi (Frontiers in neuroscience, 2016)
In healthy subjects, dual hemisphere transcranial direct current stimulation (tDCS) over the primary (S1) and secondary somatosensory cortices (S2) has been found to transiently enhance tactile performance. However, the effect of dual hemisphere tDCS on tactile performance in stroke patients with sensory deficits remains unknown. The purpose of this study was to investigate whether dual hemisphere tDCS over S1 and S2 could enhance tactile discrimination in stroke patients. We employed a double-blind, crossover, sham-controlled experimental design. Eight chronic stroke patients with sensory deficits participated in this study. We used a grating orientation task (GOT) to measure the tactile discriminative threshold of the affected and non-affected index fingers before, during, and 10 min after four tDCS conditions. For both the S1 and S2 conditions, we placed an anodal electrode over the lesioned hemisphere and a cathodal electrode over the opposite hemisphere. We applied tDCS at an intensity of 2 mA for 15 min in both S1 and S2 conditions. We included two sham conditions in which the positions of the electrodes and the current intensity were identical to that in the S1 and S2 conditions except that current was delivered for the initial 15 s only. We found that GOT thresholds for the affected index finger during and 10 min after the S1 and S2 conditions were significantly lower compared with each sham condition. GOT thresholds were not significantly different between the S1 and S2 conditions at any time point. We concluded that dual-hemisphere tDCS over S1 and S2 can transiently enhance tactile discriminative task performance in chronic stroke patients with sensory dysfunction.